The study of gender in post-Soviet society: western perspectives and cultural differences - Uzma Rehman (Research Journal of Psychology, 2024)
This article is based on seven years of teaching experience and seven years of study in gender studies in modern Russia. During the initial years of the 1990s, the concepts of gender, feminism, and women's subjectivity were first introduced to the Russian population. The incorporation of Western concepts and theories has played a significant role in the advancement of gender studies in Russia. This essay explores the development of gender studies within the framework of the "Russia – West" dichotomy in Russian gender studies. It analyzes the evolution of gender studies over the course of the last ten years, considering contextual variations and the emergence of different theoretical viewpoints. Keywords: Gender studies, the "Russia vs. the West" dichotomy, and theoretical methods to gender study are all things that are talked about.